Pengaruh Model Pembelajaran Kontekstual (CTL) Dalam Meningkatkan Hasil Belajar Siswa Kelas V SDN 04 Desa Laut Tador - Harahap, Nurhalizah Alfun Sifa; Weni Prasita; Anissa Siregar; Ihsanadi; Waizul Qorni (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The focus of this research is to describe: The Effect of Contextual Learning (CTL) Model in Improving Student Learning Outcomes in Class V SDN 04 Laut Tador Village. Contextual teaching and learning-based model is a learning effort that is very helpful for teachers in linking the material to be taught with the real world of fifth grade students in the Laut tador Village. The purpose of this contextual teaching and learning-based model is to equip students with knowledge that can be flexibly divided from one problem to another from different contexts. This research is a qualitative research with descriptive method. Data collection is done through observation, interviews, and deepening of theory from several contributor who involved in research and documentation. In general, the results of this study indicate that: the contextual teaching and learning-based model has a significant effect on fifth grade students, which students are the center of learning activities and the teacher's role is only as a motivator and facilitator, so the enthusiasm of students is increasing by using this learning model. In the implementation of contextual teaching and learning-based model, it cannot be separated from the intervention of teachers and students in classes, schools, and institutions for the better learning experience and affective learning management.